2016
DOI: 10.1186/s13048-016-0223-1
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic ovarian transplantation results in less apoptosis than orthotopic transplantation in a minipig model

Abstract: BackgroundOvarian autotransplantation has shown increasing promise as a clinical method for the preservation of fertility and hormonal function. However, information regarding the success rate of this type of transplantation is limited. We hypothesized that results vary according to the site of the ovarian transplantation. To test this hypothesis, fresh or cryopreserved ovarian strips were autotransplanted to orthotopic or heterotopic sites. The strips were later collected, and the morphology and expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Improving techniques led to an estimated 35%-40% live birth [49], since the first alive human baby, obtained as a result of ovarian cortex auto-transplant, was reported in 2004, and there were more than 100 live births worldwide; however, global reach of the procedure remains low, limiting further progress [49]. There are growing numbers of studies trying to discern how the best results can be obtained, by ovarian strip vitrification, or slow freezing, whole ovary versus ovarian strip, or the best place to insert the implant as one study concluded that implant location could significantly affect the results [50]. One group [51] compared whole ovary vitrification vs. slow freezing and concluded that the efficacy of whole ovaries cryopreservation by vitrification was higher than those by conventional freezing and rapid freezing, and that conventional freezing of ovarian cortical strips was more effective than cryopreservation of whole ovaries, independent of the way of whole ovary cryopreservation.…”
Section: New Techniques Of Fertility Preservationmentioning
confidence: 99%
“…Improving techniques led to an estimated 35%-40% live birth [49], since the first alive human baby, obtained as a result of ovarian cortex auto-transplant, was reported in 2004, and there were more than 100 live births worldwide; however, global reach of the procedure remains low, limiting further progress [49]. There are growing numbers of studies trying to discern how the best results can be obtained, by ovarian strip vitrification, or slow freezing, whole ovary versus ovarian strip, or the best place to insert the implant as one study concluded that implant location could significantly affect the results [50]. One group [51] compared whole ovary vitrification vs. slow freezing and concluded that the efficacy of whole ovaries cryopreservation by vitrification was higher than those by conventional freezing and rapid freezing, and that conventional freezing of ovarian cortical strips was more effective than cryopreservation of whole ovaries, independent of the way of whole ovary cryopreservation.…”
Section: New Techniques Of Fertility Preservationmentioning
confidence: 99%
“…Nevertheless, heterotopic transplantation has benefits such as easier access, relatively simpler transplantation procedure, and cost‐effectiveness in cases of repeated transplantations (J. Donnez et al, ). Heterotopic grafts' long‐term restoration of endocrine function has been demonstrated, and a recent study reported that heterotopic grafts cause less apoptosis than orthotopic grafts (Damasio et al, ; S. S. Kim, ). More studies are needed to identify the appropriate transplantation sites; however, orthotopic transplantation is deemed to satisfy the ideal concept of the artificial ovary as it allows natural ovulation and pregnancy.…”
Section: Transplantation Sites and Surgical Considerationsmentioning
confidence: 99%
“…Donnez et al, 2013). Heterotopic grafts' long-term restoration of endocrine function has been demonstrated, and a recent study reported that heterotopic grafts cause less apoptosis than orthotopic grafts (Damasio et al, 2016;S. S. Kim, 2012).…”
Section: When Heterotopic Transplantation Is Conducted Several Factorsmentioning
confidence: 99%
“…According to Kim (2012;2014), the heterotopic graft produced progesterone secretion. A recent paper (Damásio et al, 2016) reported that heterotopic transplantation was able to preserve ovarian follicle integrity in an animal model, but the manuscript failed to report endocrine secretion. In a study by Suzuki et al (2012), it was reported that heterotopic autografts can give rise to long-term ovarian function, with progesterone values over 10 mg/ml during the luteal phase.…”
Section: Kimmentioning
confidence: 99%